Cytidine deaminase enables Toll-like receptor 8 activation by cytidine or its analogs. (10th December 2018) - Furusho, Katsuhiro; Shibata, Takuma; Sato, Ryota; Fukui, Ryutaro; Motoi, Yuji; Zhang, Yun; Saitoh, Shin-ichiroh; Ichinohe, Takeshi; Moriyama, Masafumi; Nakamura, Seiji; Miyake, Kensuke
Abstract : Cytidine deaminase enhances TLR8 sensing of nucleosides Abstract: Toll-like receptor 8 (TLR8), a sensor for pathogen-derived single-stranded RNA (ssRNA), binds to uridine (Uri) and ssRNA to induce defense responses. We here show that cytidine (Cyd) with ssRNA also activated TLR8 in peripheral blood leukocytes (PBLs) and a myeloid cell line U937, but not in an embryonic kidney cell line 293T. Cyd deaminase (CDA), an enzyme highly expressed in leukocytes, deaminates Cyd to Uri. CDA expression enabled TLR8 response to Cyd and ssRNA in 293T cells. CDA deficiency and a CDA inhibitor both reduced TLR8 responses to Cyd and ssRNA in U937. The CDA inhibitor also reduced PBL response to Cyd and ssRNA. A Cyd analogue, azacytidine, is used for the therapy of myelodysplastic syndrome and acute myeloid leukemia. Azacytidine with ssRNA induced tumor necrosis factor-α expression in U937 and PBLs in a manner dependent on CDA and TLR8. These results suggest that CDA enables TLR8 activation by Cyd or its analogues with ssRNA through deaminating activity. Nucleoside metabolism might impact TLR8 responses in a variety of situations such as the treatment with nucleoside analogues.